Enhancing Fiqh Learning Outcomes through 3D Animated Videos: A Study of 'Upin & Ipin' at MTsN (State Islamic Junior High School) - Maulana Firdaus , Ratio; Anwar, Khoirul; Fadilah, M. Risky (Al-Tadzkiyyah: Jurnal Pendidikan Islam, 2026)
This study aims to improve the learning outcomes of Fiqh on ablution material through the use of 3D animated video media "Upin and Ipin" at Madrasah Tsanawiyah Negeri 5 Jambi City. The background of this study is the low absorption of students towards procedural materials and the lack of variety of learning media used by teachers. The method used is Classroom Action Research (CAR) consisting of two cycles, with research subjects totaling 25 students of class VII B. Data were collected through learning outcome tests, student activity observation sheets, and interviews. The results of the study showed a significant increase in learning outcomes gradually. In the pre-cycle stage, the percentage of students learning completeness was only 44% with an average score of 73.20. After the actions were carried out in Cycle I, the completeness increased to 64% with an average score of 81.80. In Cycle II, through improved guidance techniques and more intensive use of media, learning completeness reached 84% with an average score of 87.20. In addition, student learning activities increased from the sufficient category to very good. The conclusion of this study is that the use of 3D animated video media "Upin and Ipin" is effective in improving students' Fiqh learning outcomes because it is able to visualize the material concretely and create a pleasant learning atmosphere (joyful learning). These findings recommend educators to integrate audio-visual technology in the learning of practical worship materials at the Madrasah Tsanawiyah level.